2011
DOI: 10.1002/ardp.201100212
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazonoyl Halides as Precursors for New Fused Heterocycles of 5α‐Reductase Inhibitors

Abstract: A new series of benzo[6,7]cyclohepta[1,2-d]triazolo[4,3-a]pyrimidines 8a-l was synthesized via reaction of heterocyclic thione 4 or its methyl derivatives 10 with hydrazonoyl halides 5a-l. Also, reaction of compound 4 with a mixture of chloroacetic acid and aromatic aldehyde derivatives gave benzo[6,7]cyclohepta[1,2-d]thiazolo[3,2-a]pyrimidin-3-ones 12-14. The microanalyses and spectral data of the synthesized compounds are in full agreement with their molecular structure. All the newly synthesized products we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Recently, we published the antimicrobial activity results of a series of N -[3-aryl-5-(3-dimethylamino-acryloyl)-3 H -[1,3,4]-thiadiazol-2-ylidene]-benzamides, which showed promising activity [ 11 ]. Based on these findings, and in continuation of our interest in synthesis of bioactive compounds [ 12 , 13 , 14 , 15 , 16 ], we have now prepared a new series of 1,3,4-thiadiazoles via reaction of N -[3-aryl-5-(3-dimethylamino- acryloyl)-3 H -[1,3,4]-thiadiazol-2-ylidene]-benzamides with 1,3-dipoles and some nitrogen nucleophiles to investigate the antimicrobial activity of the products and study their structure activity relationship (SAR) towards some microorganisms.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, we published the antimicrobial activity results of a series of N -[3-aryl-5-(3-dimethylamino-acryloyl)-3 H -[1,3,4]-thiadiazol-2-ylidene]-benzamides, which showed promising activity [ 11 ]. Based on these findings, and in continuation of our interest in synthesis of bioactive compounds [ 12 , 13 , 14 , 15 , 16 ], we have now prepared a new series of 1,3,4-thiadiazoles via reaction of N -[3-aryl-5-(3-dimethylamino- acryloyl)-3 H -[1,3,4]-thiadiazol-2-ylidene]-benzamides with 1,3-dipoles and some nitrogen nucleophiles to investigate the antimicrobial activity of the products and study their structure activity relationship (SAR) towards some microorganisms.…”
Section: Introductionmentioning
confidence: 90%
“…We previously reported that when thiosemicarbazide derivative reacts with hydrazonoyl chlorides in dioxane in the presence of triethylamine, a cyclic product like 12 is formed [30]. However, when thiosemicarbazide derivatives 5a,b react with hydrazonoyl chlorides 9a-c, it affords compounds 13a-e rather than the expected analog of 12.…”
Section: Resultsmentioning
confidence: 99%
“…Another active heterocyclic ring system is triazolopyrimidine derivatives, which are known by their activities as antimicrobial , antitumor and analgesic, and anti‐inflammatory . Encouraged by all these findings and in continuation of our program focusing on the synthesis of bis ‐heterocyclic compounds that expected to be biologically active , we reported in the present work an efficient and rapid method for the synthesis of a series of bis ‐thiazole and bis ‐triazolopyrimidine derivatives from the titled aldehyde. The synthesized bis‐ compounds will be attractive species for the medicinal researchers to investigate their biological activity.…”
Section: Introductionmentioning
confidence: 85%